HEMBUSAN POLITIK BAU DI âPENJARA SUCI MATAHARI TERBITâ: PRAKTIK KONSUMSI WEWANGIAN SISWI MADRASAH MUALLIMAAT MUHAMMADIYAH YOGYAKARTA - , Maulida, Dr. S. Bayu Wahyono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Aroma is a social phenomenon that embedded certain value and meaning from various culture. Fragrance use prohibition in Madrasah Mu'allimaat Muhammadiyah becomes an entrance to reveal how aroma matter was defined by female student and authority holder of madrasah.Although strict policies rule student's performance (including how to use fragrance), on the other hand, domination of artificial product is found in everyday life in student's boarding house.Research is conducted to explore practice and motive of fragrance use by female student. Beside that, this research will explain about fragrance discourse that operated among female student, which related to various factor.To reach those aims, this research used new ethnography approach by Saukko as methodology base with method of participatory and non-participatory observation. The collected data is analyzed by Goffman'stheory of body management and social interaction. The data is also analyzed by Gramsci's theory of Hegemony and Counter Hegemony to uncover the meaning of fragrance among female student which became contested site between religious school and market institution.Based on the analysis about fragrance consumption of female student, data gathered shows that first, fragrance was interpreted by female student as instrument of impression and relation. Second, fragrance use by female student is considered as everyday resistance towards âpolitic of madrasah smellâ (prohibition of fragrance use upon female student which is legitimated by religious text). Third, permissiveness towards âartificial fragrances blowâ by the girls could not be separated from the media discourse that construct. Therefore, it is not directly form a preference of the scent of an agreed concept, namely artificial fragrances, thus âblowingâthe scent outside the âdealâ (the body's natural scent) tend to be excluded. Keywords: smell politics, female student, madrasah, resistance, hegemony